The Significance of TFPI in Clotting Assays – Gomparison and Combination with other Anticoagulants - Nordfang, Ole; Kristensen, Hanne I; Valentin, Sanne; Østergaard, Per; Wadt, Johnny (Thrombosis and Haemostasis, 1993)
The anticoagulant activities of Tissue Factor Pathway Inhibitor (TFPI), heparin and hirudin were compared in intrinsic (APTT) and extrinsic (PT) activated clotting assays. In contrast to the thrombin inhibitor hirudin, heparin was 10 fold more potent in the APTT assay than in the PT assay, indicating that inhibition of intrinsic activation is important for the anticoagulant activity of heparin as measured in an APTT assay. TFPI was most potent in the PT assay and the effect of TFPI was most pronounced in the presence of other anticoagulants (heparin and hirudin). The activities of the two natural anticoagulants antithrombin III (ATIII) and TFPI were compared in a PT assay with very dilute tissue factor. In this assay system TFPI in normal plasma affected the clotting time more than ATIII in the plasma. However, when heparin was added ATIII was the major anticoagulant, but profound Prolongation of the clotting time was only seen when TFPI was also added. In an ATIII deficient plasma heparin did not augment the effect of TFPI, showing that the increased effect of TFPI in the presence of heparin is dependent on the anticoagulant activity of ATIII/heparin. The effect of TFPI at prolonged clotting times was also illustrated by the significant effect of blocking TFPI in the plasma from warfarin-treated patients. Thus TFPI is a major anticoagulant in normal plasma and the effect of TFPI is especially seen at prolonged clotting times.